Complete solution of the one-dimensional Hubbard model. - Essler, F; Korepin, V; Schoutens, K (1991)
We show how to construct a complete set of eigenstates of the Hamiltonian of the one-dimensional Hubbard model on a finite lattice of even length L. This is done by using the nested Bethe ansatz and the SO(4) symmetry of the model. © 1991 The American Physical Society.